The Gel Soap with Raw Materials of Lerak Fruit (Sapindus rarak DC) - Fitria Wijayanti; Mayang Sari; Roni Suprayitno; Dian Aminin (Department of Chemistry - Universitas Bangka Belitung, 2020)
Lerak (sapindus rarak DC) is one of the plants that is often used as a noble metal washer, facial cleanser as a remover for acne and as an insecticide, especially earthworms. In this study the manufacture of soap gel by using Lerak plants. Lerak fruit (Sapindus rarak DC) is one of the natural ingredients that can be used as an alternative in soap raw materials. Lerak fruit (S. rarak) contains several secondary metabolites. The most dominant secondary metabolite is saponin. These saponins act as raw material for making soap. The purpose of this study is the use of natural materials, especially Lerak fruit as raw material for gel soap Tests conducted on soap are foam test, soap quality with experiments on several stains and organoleptic soap tests. The results obtained Lerak fruit can be used as raw materials for soap. The foam test results on the soap found that the soap foaming durability was longer. The results of soap quality testing on several stains namely charcoal stains, soy sauce stains and sauces prove the soap can clean stains well. The organoleptic results get a distinctive aroma, odor, and average of density are 1.01.